Simulation of agricultural systems - Portugal, Alberto Duque (Pesquisa Agropecuaria Brasileira, 2014)
This paper aimed at contributing to the greater knowledge of system simulation as a research technique to be used in agriculture. It presents concepts of system, models, simulation, and related terms, emphasizing advantages and limitations of that technique; it defines different types of models and describes the main steps in simulation. It is concluded that system simulation is a technique with a great potential but that it shows difficulties which demand a high level of judgment, creativity and integrity.